Hikikomori and Sōshokukei-danshi: A semantic analysis of Japan's social deviants - Natasha McFarlane (Peoples' Friendship University of Russia (RUDN University), 2024)
This study is a semantic analysis that examines the meanings of two contemporary Japanese labels, hikikomori and soushokukei-danshi. This duo has often been linked to the late marriage age, declining marriage rate, shoushika (low birth rate), and koureika (the aging society). The goal of this thesis is to define these individuals according to the perceptions of native Japanese speakers and to convey the definitions by using the reductive paraphrase methodology. Accordingly, cultural values reflected in the labels will be revealed. The Natural Semantic Metalanguage (NSM) approach and corpus analysis are the chosen methodology. NSM is a universal mini metalanguage, while corpus analysis is a tool that can analyse data from online sources. Combined, these methods support the goal of delivering explications that reflect the labels from a Japanese perspective. Results from the study show that the values of Japanese society and the duos are at odds with one another, subsequently, fuelling the negative stigma directed towards both cohorts: Hikikomori are individuals who are emotionally withdrawn and bound to the house for the most part. Furthermore, their condition is something they feel they cannot change so easily; and Soushokukei-danshi are young men who are uninterested in romance or attaining stereotypical male positions in the workforce. Moreover, they would rather invest time in their hobbies. Through this study, a better comprehension of what these words mean is acquired.